Morphometric Analysis of Coronoid Process of Mandible by CT in the Malaysian Population: An Important Step for Determination of Sex - Aspalilah Alias; Abdel Nasser Mohamad Ibrahim; Siti Noorain Abu Bakar; Faezah Rokhani; Mohamed Swarhib Shafie; Faridah Mohd Nor (MS INNOVARE ACADEMIC SCIENCES PRIVATE LIMITED, 2025)
Journal of Dental Sciences Research and Therapy, Volume 1 Issue 1